2023
DOI: 10.4236/aim.2023.134010
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Biofilm, Anti-Quorum Sensing, and Anti-Proliferative Activities of Methanolic and Aqueous Roots Extracts of <i>Carica papaya</i> L. and <i>Cocos nucifera</i> L.

Abstract: Objective: This study focused on the antibacterial and anti-proliferative activity of extracts from Carica papaya and Cocos nucifera roots. Methodology:The minimum inhibitory concentration and the minimum bactericidal concentration of the extracts on Escherichia coli, Pseudomonas aeruginosa, Streptococcus mutans, and Staphylococcus aureus were deduced by the microdilution method. The anti-biofilm activity was determined on all four strains and anti-quorum sensing activity by inhibition of violacein production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Anti-biofilm activity of certain medicinal plants against S. mutans has been studied previously. Belem-Kabré et al reported that at a concentration of 100 μg/mL, the methanolic extract of Carica papaya suppressed 66.10% of the biofilm produced by S. mutans [14]. Murugan et al reported that the methanol extract of Achyranthes aspera (125 g/mL) produced biofilm inhibition of 94% [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-biofilm activity of certain medicinal plants against S. mutans has been studied previously. Belem-Kabré et al reported that at a concentration of 100 μg/mL, the methanolic extract of Carica papaya suppressed 66.10% of the biofilm produced by S. mutans [14]. Murugan et al reported that the methanol extract of Achyranthes aspera (125 g/mL) produced biofilm inhibition of 94% [15].…”
Section: Discussionmentioning
confidence: 99%
“…One of these strategies can be using the various medicinal plants available [6]. Also, research on the anti-QS activity of medicinal plants has been rapidly increasing in recent years [14,15]. Evaluation of anti-QS and anti-biofilm activity of Murraya koenigii and Terminalia catappa against S. mutans can be done as both these plants have shown good antibacterial activity against S. mutans.…”
Section: Introductionmentioning
confidence: 99%